2018
DOI: 10.1262/jrd.2018-055
|View full text |Cite
|
Sign up to set email alerts
|

IRS2 depletion inhibits cell proliferation and decreases hormone secretion in mouse granulosa cells

Abstract: Insulin receptor substrate 2 (IRS2) is a component of the insulin/insulin-like growth factor 1 (IGF1) signaling cascade, which plays an important role in mouse hypothalamic and ovarian functions. The present study was conducted to investigate the role of IRS2 in steroidogenesis, apoptosis, cell cycle and proliferation in mouse granulosa cells (GCs). Flow cytometry and CCK8 assay showed that IRS2 knockdown inhibited cell proliferation, reduced cell viability, and increased apoptosis in GCs. The study also revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Upon APC/C inactivation at the G1/S boundary, IRS2 is able to accumulate and stimulate 374 signaling required for normal progression through the latter stages of the cell cycle, 375 including the expression of proteins required for mitotic spindle checkpoint function. This 376 model is consistent with previous studies that implicate IRS2 in promoting the expression 377 of cell cycle-related genes, including mitotic cyclins (A and B) in mouse granulosa cells 378 (Lei et al, 2018). Furthermore, IR signal transduction promotes the expression of Plk1 (a 379 mitotic kinase) and CENP-A (a centromere protein) in β cells through a mechanism that 380 appears to depend on IRS2 rather than IRS1 (Folli et al, 2011;Shirakawa et al, 2017).…”
Section: Irs2 Expression Promotes a Functional Spindle Assembly Checksupporting
confidence: 84%
“…Upon APC/C inactivation at the G1/S boundary, IRS2 is able to accumulate and stimulate 374 signaling required for normal progression through the latter stages of the cell cycle, 375 including the expression of proteins required for mitotic spindle checkpoint function. This 376 model is consistent with previous studies that implicate IRS2 in promoting the expression 377 of cell cycle-related genes, including mitotic cyclins (A and B) in mouse granulosa cells 378 (Lei et al, 2018). Furthermore, IR signal transduction promotes the expression of Plk1 (a 379 mitotic kinase) and CENP-A (a centromere protein) in β cells through a mechanism that 380 appears to depend on IRS2 rather than IRS1 (Folli et al, 2011;Shirakawa et al, 2017).…”
Section: Irs2 Expression Promotes a Functional Spindle Assembly Checksupporting
confidence: 84%
“…Compared with the control treatment, PA treatment decreased E2 and P4 expression. The possible reason for the reductions could be the decreases in the levels of Star (the protein associated with the transport of cholesterol across the mitochondrial membrane), Cyp11a1 (the monooxygenase that catalyzes cholesterol and steroid synthesis), and Cyp19a1 (the enzyme responsible for androgen aromatization to estrogen) [31] shown in our results. Previous studies have demonstrated that E2 and P4 are indispensable for maintaining the normal physiological function of the ovary [44].…”
Section: Discussionmentioning
confidence: 99%
“…Immature female mice ( n = 285) were intraperitoneally injected with 8 IU pregnant mare serum gonadotrophin (PMSG) (Ningbo Sansheng, Ningbo, China) to facilitate granulosa cell proliferation. After 44 h, primary mouse granulosa cells were isolated and cultured as described previously [31]. Briefly, the ovaries were collected, and granulosa cells were released by puncturing the follicles with 26-gauge needles under sterile conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The IRS proteins are the classical substrates for insulin and IGF1 receptor tyrosine kinases, which play an important role in normal physiological activities [4]. IRS2 is known to mediate metabolic homeostasis [5] and plays an important role in ovarian functions [6]. Moreover, some studies have emphasized its role in growth and proliferation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have emphasized its role in growth and proliferation [7,8]. In addition, IRS2 can also regulate cell functions, including cell survival, steroidogenesis, and cell differentiation through the PI3K/AKT signaling pathway [6].…”
Section: Introductionmentioning
confidence: 99%